Role of Quantitative Apparent Diffusion Coefficient in Predicting Genetic Subtypes of Gliomas - Kajan Ranabhat; Suresh Bishokarma; Pratyush Shrestha; Rajesh Panth; Ram Kumar Ghimire (Nepal Journal of Neuroscience, 2020)
Introduction: Magnetic resonance morphologic features are widely used in characterising gliomas for predicting grades and thereby aiding in preoperative management planning. We aim to find out if Magnetic Resonance Imaging (MRI) morphologic characters and quantitative apparent diffusion coefficient (ADC) measurements can predict genetic subtypes of high-grade gliomas.